Reflective practice and work-based research: a description of micro- and macro-reflective cycles. Issue 2 (4th March 2019) - Fergusson, Lee; van der Laan, Luke; Baker, Shayne
ABSTRACT: The role and importance of reflective practice have been thoroughly documented and its benefits are well established. When coupled with research in a higher education context, a similar importance for reflection can be extended to professional development, leadership, and work-based learning. However, the relation of reflective practice to work-based research, specifically when defined as an element of methodology in higher degree research awards, has yet to be fully examined. In this paper, we explore the basic principles of reflective practice as they relate to work-based learning and highlight the interfaces or 'bridges' between reflective cycles, showing their centrality to work-based research. As an example of how these principles might be applied, we also introduce the role of each micro- and macro-reflective cycle in the Professional Studies program at University of Southern Queensland, a relatively new academic approach which utilises both work-based learning and work-based research.